2012
DOI: 10.2106/jbjs.j.01077
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Comorbidities on Hospitalization Costs Following Hip Fracture

Abstract: Comorbidities significantly affect the cost of hospitalization and length of stay following hip fracture in older Americans, even while controlling for other variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
112
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 162 publications
(128 citation statements)
references
References 21 publications
12
112
0
4
Order By: Relevance
“…Overall, the AUC values for inpatient mortality for the Charlson and Elixhauser comorbidity-based measures in our study were comparable to or slightly higher than those described in other patient populations [6,18,27,52]. Consistent with a study by Nikkel et al [39] in patients with hip fractures, the Elixhauser weight loss or malnutrition comorbidity was the major factor influencing mortality. We found some comorbidities (eg, hypothyroidism, obesity, uncomplicated diabetes, hypertension) to be associated with decreased odds of inpatient mortality.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Overall, the AUC values for inpatient mortality for the Charlson and Elixhauser comorbidity-based measures in our study were comparable to or slightly higher than those described in other patient populations [6,18,27,52]. Consistent with a study by Nikkel et al [39] in patients with hip fractures, the Elixhauser weight loss or malnutrition comorbidity was the major factor influencing mortality. We found some comorbidities (eg, hypothyroidism, obesity, uncomplicated diabetes, hypertension) to be associated with decreased odds of inpatient mortality.…”
Section: Discussionsupporting
confidence: 90%
“…First, the NHDS dataset is based on billing data from ICD-9-CM codes, and such a coding system may not fully capture the patient population of interest [1]. In particular, it has been suggested that administrative databases tend to underreport chronic medical conditions that are considered less acute in the perioperative orthopaedic surgery setting [16,31,33,34,39]. Second, the possibility of errors in coding of the diagnoses and procedures cannot be avoided [7]; however, misclassification mistakes distribute evenly in large-scale studies [53].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations